2011
DOI: 10.4103/0256-4947.78206
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of human Ewing/PNET sarcoma models

Abstract: Ewing/PNET (peripheral neuroepithelioma) tumors are rare aggressive bone sarcomas occurring in young people. Rare-disease clinical trials can require global collaborations and many years. In vivo models that as accurately as possible reflect the clinical disease are helpful in selecting therapeutics with the most promise of positive clinical impact. Human Ewing/PNET sarcoma cell lines developed over the past 45 years are described. Several of these have undergone genetic analysis and have been confirmed to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…In contrast to localized cases of ES, advances in standard treatment approaches have not been encouraging with regard to improving the survival rates for metastatic and recurrent cases, as 5-year survival rates have recently been described as less than 25% [8, 62, 63]. It has been suggested that chemotherapy and radiation treatments are reaching their efficacy and toxicity limits [83].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to localized cases of ES, advances in standard treatment approaches have not been encouraging with regard to improving the survival rates for metastatic and recurrent cases, as 5-year survival rates have recently been described as less than 25% [8, 62, 63]. It has been suggested that chemotherapy and radiation treatments are reaching their efficacy and toxicity limits [83].…”
Section: Discussionmentioning
confidence: 99%
“…All three forms of treatments have shown efficacy in some cases [52]. Most current therapies call for multidrug chemotherapy, consisting of cycles of varied combinations of vincristine, doxorubicin, cyclophosphamide, etoposide, ifosfamide, actinomycin D, and topotecan, followed by local therapies (radiation and/or surgery) [8, 53]. …”
Section: Clinical Approaches and Targeted Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Occasionally, epithelial markers and desmin might show focal positivity, whereas the expression of neural markers such as NSE, S-100, neurofilaments, glial fibrillary acid protein, and CgA is uncertain. A characteristic chromosomal translocation t(11;22)(q24;q12), resulting in EWS–FLI1 fusion, is observed in 85% of PNET cases;14,15 most of the remaining cases (10%–15%) show fusion of the EWS gene to a second member of the ETS family of genes, namely ERG. EWS–ERG fusion occurs as a result of the chromosomal translocation t(21;22)(q22;q12) 12…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal translocations characterize many types of cancers [1], [2] and also can become useful markers in the diagnosis of liquid and solid tumors [3], [4]. However, the molecular factors that elicit this gross chromosomal rearrangement (GCR) are still object of investigation [5], [6].…”
Section: Introductionmentioning
confidence: 99%